Developing and Organizing an Easy Work Environment for Users of Computers Using Information Technology - Aloubade, Yasir Khudheyer Abass (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
The study aims to implement a serial security technology system to organize a comfortable work environment for users of computers in the General Directorate of Education in Baghdad Karkh3. The most important findings of the study are the application of a serial technology system. It is connected with scientific goals that show the scientific structure of computer learning and its applications.  It considers global learning systems and take into account the ease and scientific flow of the class of elderly employees. In addition, employees of other categories, are the outputs of the sequential technological system. The aim is to create a purposeful technological system and keep pace with global developments, to gain experience, skills and knowledge. The system is executed at the lowest time and cost at all different scientific levels, in the field of computer science, information technology, and communication.